DIGITAL KINK OPACITY: SEXUAL SOCIAL MEDIA BEYOND VISIBILITY AND COMPREHENSION - Sundén, Jenny (AoIR Selected Papers of Internet Research, 2023)
Building on and expanding discussions of the value of anonymity and pseudonymity in digital cultures in general, and in queer digital cultures in particular, this paper explores notions of opacity as modes of resistance to dominating regimes of visibility on and beyond social media platforms. Across queer, postcolonial and digital media theorizing, opacity provides a way of thinking through the tension between the visible and the invisible, challenging the idea of public visibility and identification as that which drives data cultures and legitimizes deviant sexual practices and expressions. Suggestive of discussions on tactical, queer uses of social media in terms of disconnection and reluctance, opacity affords yet another way of thinking resistance to platform power and user control. Based on an ethnographic study of the Swedish digital BDSM, fetish and kink platform Darkside, this paper theorizes opacity in two ways: first, as a way of discussing tactical uses of Darkside between modes of revealing and concealing, and second, as a way of conceptualizing the platform as a borderland between intelligibility and unintelligibility. Opacity implies a lack of clarity; something opaque may be both difficult to see clearly as well as to understand. Drawing on Édouard Glissant (1997) and his idea of “the right to opacity” as a form of resistance to surveillance and imperial domination, a digital sexual politics of opacity could help provide recognition without a demand to fully understand sexual otherness, opening up for new modes of obscure and pleasurable sexual expressions and transgressions on social media platforms.